2022
DOI: 10.3390/ijerph19159707
|View full text |Cite
|
Sign up to set email alerts
|

Binge-Watching and Mental Health Problems: A Systematic Review and Meta-Analysis

Abstract: Background: Binge-watching, the viewing of online videos or streamed content, may be associated with different types of mental health problems. The present study aimed to investigate the associations between binge-watching and five mental health concerns including depression, loneliness, sleep problems, anxiety, and stress. Methods: Academic databases of PubMed, Scopus, Web of Science, ProQuest, PsycINFO, and Psych Articles were systematically searched through February of 2022. The Newcastle–Ottawa Scale was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Based on previous findings indicating that problematic video gaming (Bányai et al, 2019; Király, Tóth, et al, 2017), social media use (Hussain & Griffiths, 2018; Marino et al, 2020), and binge-watching (Aghababian et al, 2021; Alimoradi et al, 2022) are associated with mental health symptoms such as depression, anxiety, and distress, we investigate the relationship between Twitch use patterns and psychological correlates in Study 2. Another potential correlation could be maladaptive daydreaming, which involves excessive fantasizing, an activity that shares some common features with behavioral addictions (e.g., loss of control; Somer, 2002).…”
Section: The Popularity Of Twitch and Current Research Perspectivesmentioning
confidence: 99%
“…Based on previous findings indicating that problematic video gaming (Bányai et al, 2019; Király, Tóth, et al, 2017), social media use (Hussain & Griffiths, 2018; Marino et al, 2020), and binge-watching (Aghababian et al, 2021; Alimoradi et al, 2022) are associated with mental health symptoms such as depression, anxiety, and distress, we investigate the relationship between Twitch use patterns and psychological correlates in Study 2. Another potential correlation could be maladaptive daydreaming, which involves excessive fantasizing, an activity that shares some common features with behavioral addictions (e.g., loss of control; Somer, 2002).…”
Section: The Popularity Of Twitch and Current Research Perspectivesmentioning
confidence: 99%
“…[4] Research has shown that binge-watching is signi cantly associated with stress & anxiety. [5,6] Escapism, enrichment, emotional enhancement, and social are the four primary reasons for bingewatching. Escapism is the urge to run away from the real world and everyday challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, another possible BA, referred to as binge-watching (BW), is characterized by the concept of multiple episodes of TV content in a single session, usually alone, with reduced social interactions during the experience [ 10 ]. Regardless of their features on social interaction, both behaviors affect mental health positively and negatively to different degrees [ 11 , 12 ]. However, from these preliminary definitions, it seems evident that characteristics of interpersonal interactions could differently influence the continuum of each behavior.…”
Section: Introductionmentioning
confidence: 99%